Programming DNA cascade circuits on live cell membranes for accurate cancer cell recognition and gene silencing. Issue 31 (19th March 2021) - Wang, Xiangnan; Liu, Lan; Wu, Han; Wu, Zhenkun; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : A programmable and activatable DNA cascade circuit has been developed on live cell membranes for accurate cancer cell identification and precise gene silencing via dual-aptamer based AND logic operations. Abstract : A dual-aptamer based AND logic cascade circuit is activated on cell membranes in response to the receptor–aptamer binding, affording enhanced specificity for cell subtype recognition and gene silencing.